Simulation of proton diffusion in In-doped CaZrO3 - Bilic, Ante; Gale, Julian (Elsevier, 2008)
First principles calculations, based on density functional theory, are exploited to investigate the mechanisms and energetics of proton mobility in In-doped CaZrO3. Binding sites for protons in the crystal are provided for a range of local In concentrations. A set of proton transfer hops is identified and associated energy barriers for these proton steps are computed. The calculated lowest energy paths that lead to proton propagation in CaZrO3 exhibit energy barriers in excess of 0.6 eV. Together with previously reported activation energies for proton reorientations and attempt frequencies for proton moves, the present results provide a comprehensive set of data from which the rates of proton migration in In:CaZrO3 may be determined. The use of the data in kinetic Monte Carlo simulations at 1160 K reveals slightly higher proton mobility in In-doped crystal than in the pure CaZrO3. This suggests that dopant-proton trapping, expected from larger binding strengths at In octahedra by 0.1-0.2 eV, is relatively weak and short-ranged.